Rediscovery of Hibiscus surattensis L. (Malvaceae) from the Delhi Region after more than Century - Mishra, A. K.; Mir, S. A.; Shah, A.; Sharma, M. P.; Singh, H. B. (Indian Forester, 2015)
No Abstract.